Prolonged remission from hepatic encephalopathy with rifaximin: results of a placebo crossover analysis. Issue 1 (22nd October 2014) - Bajaj, J. S.; Barrett, A. C.; Bortey, E.; Paterson, C.; Forbes, W. P.
Summary Background Rifaximin therapy reduced risk of hepatic encephalopathy (HE) recurrence and HE‐related hospitalisations during a 6‐month, randomised, placebo‐controlled trial (RCT) and a 24‐month open‐label maintenance (OLM) study. However, the impact of crossover from placebo to rifaximin therapy is unclear. Aim To study the impact of crossing over from placebo to rifaximin treatment on breakthrough HE and hospitalisation rates using a within‐subjects design. Methods Adults with cirrhosis and history of overt HE episodes, currently in HE remission, received placebo during the RCT and crossed over to rifaximin 550 mg twice daily during the OLM study. Rate of breakthrough overt HE episodes, hospitalisations and incidence and rate of adverse events (AEs) were analysed during RCT and first 6 months of OLM. Results Of 82 patients randomised to placebo in the RCT who crossed over to the OLM study, 39 experienced an HE episode during the RCT compared with 14 during the OLM study (P < 0.0001). Significantly lower rates of HE events were observed with rifaximin treatment compared with placebo treatment (P < 0.0001). Rates of HE‐related hospitalisation were numerically lower during rifaximin treatment compared with placebo treatment, although not significant. Rates of most common AEs, serious AEs and infection‐related AEs were similar between the two treatments. Conclusions This analysis confirms the repeatability of results from the RCT on safety and efficacy of rifaximin 550 mg twice daily in reducing the risk of hepatic encephalopathy recurrence, and suggests these findings are translatable outside of a rigorous, controlled trial setting.